STUDI KOMPARATIF KESIAPAN GURU BERPEDAGOGI TRADISIONAL DAN MODERN DALAM MENGHADAPI PENDIDIKAN ISLAM DI ERA DIGITAL - Auliya', Hilyatul (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study analyzes the readiness, challenges, and strategies of Islamic Education (PAI) teachers in facing the digitalization of learning, comparing traditional and modern pedagogical approaches at SMP Negeri 22 Surabaya. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The findings show that teachers with modern pedagogical approaches are more digitally prepared, actively participate in online training, and are innovative in creating learning media. In contrast, traditional teachers face digital literacy challenges and tend to be passive toward change. Traditional teachers rely on limited peer collaboration, while modern teachers utilize online training, sharing communities, and independent initiatives. This study highlights the need for structured training and adequate infrastructure tailored to each pedagogical approach and provides a foundation for further research on the effectiveness of digital learning strategies in Islamic education.